Monitoring fluorine, one of priority elements of underground drinking-water of the Poltava hydrochemical province - Бойко, І. А. (Scientific Progress & Innovations, 2012)
Conformities to the law of distributing and migration of fluorine and form of its finding are considered in underground waters of the Poltava region. It is discovered that principal reason of formation of fluorine-containing waters of region is unloading of deep mineralized underground waters in the areas of tectonic activation, violations of physical and chemical equilibrium of the natural system and fluorine-containing breeds. Influence of active forms of fluorine is analyzed on a degree and character of endemics of population and the basic methods of defluorination of drinking-water are considered.